Self-Care Practices and the Associated Socio-Demographic Variables of Persons with Type 2 Diabetes Mellitus (T2dm) in Southeast, Nigeria. - Okafor, Christiana Nkiru; Okonkwo, Uchenna Prosper; Ani, Kenneth Umezulike; Onuora, Ethel Ogoemeka; Nwokike, Mathew; Byabagambi, Jane Turyasingura; Tamu, JohnBosco Munezero; Mfitumukiza, Valence; Nwankwo, Mercy Chinenye; Tumusiime, Alex (Kabale University, 2024)
Objective: The study was aimed at assessing the self-care practices and the associated socio-demographic variables of persons with T2DM in South East, Nigeria. Methodology: A cross-sectional study involving 382 persons with T2DM proportionately selected from 4 tertiary health institutions in South Eastern, Nigeria. Data was collected using the Summary of Diabetes Self-Care Activities (SDSCA) and a researcher-developed questionnaire. The questionnaire was administered to persons with T2DM who attended a diabetic outpatient clinic. Data collected was analyzed in frequency percentage. Responses on SDSCA were ranked and rated as poor, moderate, and good self-care behavior. The level of significance was placed at P < .05. Result: The majority of the participants were within the age groups of 40 to 59 (46.9%) and 60 and above (46.9%); the majority (74.6%) were married while a good proportion were traders (59.7%). Also, the majority of participants (81.2%) were on oral hypoglycemic agents. Findings further showed that a good proportion (51.3% and 89.8%) of study participants had good self-care behavior in diet and medication domains respectively. Whereas the proportion of participants with poor self-care behavior was very high in foot care (75.1%) and fairly high in both self-blood sugar testing (37.7%) and exercise (37.2%) domains. Only 7.9% practiced 3-monthly laboratory blood glucose testing while 16.5% went for eye checks every 6 months. Conclusion: Individuals with diabetes mellitus have poor self-management behavior in most domains of the self-management practice. Age, gender, marital status, educational level, and occupation significantly influenced self-management practices. Hence nurses and health educators should take diabetes self-management education very seriously to help diabetes sufferers improve their self-management